2003
DOI: 10.1176/appi.ajp.160.11.1990
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Stroop Task Study of Ventromedial Prefrontal Cortical Function in Pathological Gamblers

Abstract: Pathological gamblers share many neural correlates of Stroop task performance with healthy subjects but differ in a brain region previously implicated in disorders characterized by poor impulse control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
191
1
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 362 publications
(218 citation statements)
references
References 24 publications
18
191
1
8
Order By: Relevance
“…Conversely, some studies with PG have reported hypoactivations in vmPFC during gambling urges (eg, Potenza et al, 2003b, but cf, Goudriaan et al, 2010. Reduced activity in this region has also been reported in PG during cognitive control and monetary tasks (Balodis et al, 2012a;Potenza et al, 2003a). Across video types and diagnostic groups, women as compared with men exhibited greater activity in the Figure 3 Diagnostic group × video type interaction.…”
Section: Imaging Resultsmentioning
confidence: 62%
“…Conversely, some studies with PG have reported hypoactivations in vmPFC during gambling urges (eg, Potenza et al, 2003b, but cf, Goudriaan et al, 2010. Reduced activity in this region has also been reported in PG during cognitive control and monetary tasks (Balodis et al, 2012a;Potenza et al, 2003a). Across video types and diagnostic groups, women as compared with men exhibited greater activity in the Figure 3 Diagnostic group × video type interaction.…”
Section: Imaging Resultsmentioning
confidence: 62%
“…Another putative link between PG and OCD is the propensity of individuals who have PG to engage in excessive, possibly harmful behavior that leads to significant impairment in social or occupational functioning and causes personal distress [7]. As in OCD, the compulsive behavior of PG-gambling-is often triggered by aversive or stressful stimuli [8]. Individuals who have PG often report that their urges to gamble are triggered by feelings of anxiety, sadness, or loneliness [9,10].…”
Section: Pathological Gamblingmentioning
confidence: 99%
“…This hypothesis is intimately allied with Eysenck's (42) original notion that extroverts are chronically underaroused, more easily bored, and tend to engage in more sensation-seeking behavior. Importantly, the OFC has high DA density and is activated during the administration of DA agonists (43) and sensation-seeking behaviors (44,45). Therefore, one conclusion is that the increased modulation of the OFC results in heightened reward during humor appreciation in extroverts.…”
Section: Figmentioning
confidence: 99%